Searching for DNA Damage: Insights From Single Molecule Analysis - Schaich, Matthew A.; Van Houten, Bennett (Frontiers in Molecular Biosciences, 2021)
DNA is under constant threat of damage from a variety of chemical and physical insults, such as ultraviolet rays produced by sunlight and reactive oxygen species produced during respiration or inflammation. Because damaged DNA, if not repaired, can lead to mutations or cell death, multiple DNA repair pathways have evolved to maintain genome stability. Two repair pathways, nucleotide excision repair (NER) and base excision repair (BER), must sift through large segments of nondamaged nucleotides to detect and remove rare base modifications. Many BER and NER proteins share a common base-flipping mechanism for the detection of modified bases. However, the exact mechanisms by which these repair proteins detect their damaged substrates in the context of cellular chromatin remains unclear. The latest generation of single-molecule techniques, including the DNA tightrope assay, atomic force microscopy, and real-time imaging in cells, now allows for nearly direct visualization of the damage search and detection processes. This review describes several mechanistic commonalities for damage detection that were discovered with these techniques, including a combination of 3-dimensional and linear diffusion for surveying damaged sites within long stretches of DNA. We also discuss important findings that DNA repair proteins within and between pathways cooperate to detect damage. Finally, future technical developments and single-molecule studies are described which will contribute to the growing mechanistic understanding of DNA damage detection.